2002
DOI: 10.1111/j.1749-6632.2002.tb04058.x
|View full text |Cite
|
Sign up to set email alerts
|

Glial‐Neuronal Transfer of Arginine and S‐Nitrosothiols in Nitric Oxide Transmission

Abstract: The arginine-nitric oxide (Arg-NO) and the S-nitrosothiols systems, two less well-studied aspects of NO transmission in the central nervous system, are reviewed. A growing body of evidence suggested that they play a crucial role in NO synthesis and activity. l-Arginine, the NO precursor, is predominantly localized in glia. Together with in vitro and in vivo results of arginine release, this suggests a transfer of arginine from glia to neurons in order to supply NO synthase with its substrate. NO biosynthesis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 82 publications
0
9
0
1
Order By: Relevance
“…Recent studies have demonstrated that arginine availability is an important condition for the physiological functioning of the nitroergic system (Do et al, 2002; and Saul'skaya, 2007). Indirect reports confirm the antioxidant effects of l-arginine in the early and late stages of ischaemia (Maksimovich et al, 2006) and its reduction in brain edema formation and improvement of cortical blood flow in the early phase after a brain trauma (Lundblad and Bentzer, 2007).…”
Section: Systemic Administrationsmentioning
confidence: 93%
“…Recent studies have demonstrated that arginine availability is an important condition for the physiological functioning of the nitroergic system (Do et al, 2002; and Saul'skaya, 2007). Indirect reports confirm the antioxidant effects of l-arginine in the early and late stages of ischaemia (Maksimovich et al, 2006) and its reduction in brain edema formation and improvement of cortical blood flow in the early phase after a brain trauma (Lundblad and Bentzer, 2007).…”
Section: Systemic Administrationsmentioning
confidence: 93%
“…At low arginine concentrations, neuronal NO synthase generates NO and superoxide, favouring the production of the toxin peroxynitrite. The NMDA-induced excitotoxicity in neuronal cells is therefore dependent on the arginine availability (Do et al, 2002).…”
Section: Cellular Mechanism Of Action Of Kynureninesmentioning
confidence: 99%
“…At low arginine concentration, neuronal NO synthase generates NO and superoxide, favouring the production of the toxin peroxynitrite. Thus, the NMDA-induced excitotoxicity in neuronal cells is dependent on the arginine availability [72].…”
Section: Quin and 3-hydroxy-ana Oxygenasementioning
confidence: 99%